IMPROVING READING COMPREHENSION THROUGH DIRECTED READING THINKING ACTIVITY (DRTA) STRATEGY WITH PICTURES OF THE EIGHTH GRADE STUDENTS OF SMPN 4 MENGWI IN ACADEMIC YEAR 2020/2021 - I Ketut Alit Ngurah Ardana; Nengah Dwi Handayani; Ida Bagus Nyoman Mantra (Academic Journal on English Studies (AJOES), 2022)
Reading is considered as an essential skill in English that should be mastered by the students in all grades as well as in junior high school. On the other hand, many students faced many problems and difficulties in reading. The present classroom action research was mainly intended to figure out whether the subjects’ reading comprehension can be improved through Directed Reading Thinking Activity (DRTA) with picture. However, based on the preliminary investigation which was conducted in SMPN 4 Mengwi, it was found that most of the subjects’ reading comprehension was low and most of them could not pass the minimum passing grade, 75. It was supported by the result of pre-test which was carried out in the pre-cycle, there were 31 subjects who did the pre-test had low reading comprehension. The study was then carried out by implementing Directed Reading Thinking Activity (DRTA) With Picture in two cycles. The result of the post-test in each cycle clearly showed there was significant improvement concerning the subjects’ reading comprehension a narrative text. Furthermore, there were positive responses concerning the implementation of the technique which combined with teaching media in improving the subjects’ reading comprehension. In other words, the present study proved that reading comprehension of the eighth grade students of SMPN 4 Mengwi in academic year 2020/2021 can be improved through Directed Reading Thinking Activity (DRTA) Strategi with Picture.